2020
DOI: 10.2147/ott.s284092
|View full text |Cite
|
Sign up to set email alerts
|

<p>Complete Response to the Sequential Treatment with Regorafenib Followed by PD-1 Inhibitor in a Sorafenib-Refractory Hepatocellular Carcinoma Patient</p>

Abstract: Most patients diagnosed with hepatocellular carcinoma (HCC) have advanced diseases, and many are not eligible for curative therapies. There is growing evidence suggesting that the combination treatment of PD-1/PD-L1 inhibitors and tyrosine kinase inhibitors (TKIs) is becoming a prospective trend for advanced HCC. For those HCC patients with sorafenib resistance, the efficacy of regorafenib combined with PD-1/PD-L1 inhibitors remains unclear. Herein, we represent a case of HCC with lung metastasis in the settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Nevertheless, there is more evidence to suggest that combination therapy with PD-1/PD-L1 inhibitors and tyrosine kinase inhibitors (TKIs) is becoming a future trend in advanced HCC [34] . We think that combination loco-regional therapy with systemic therapy in unresectable HCC patients will more mature and become standardized in the next 5 years, and we believe that more studies will be conducted in the future to compare the safety and efficacy of loco-regional therapy combined with immunosuppressive agents versus sorafenib in order to maximize the clinical benefit .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is more evidence to suggest that combination therapy with PD-1/PD-L1 inhibitors and tyrosine kinase inhibitors (TKIs) is becoming a future trend in advanced HCC [34] . We think that combination loco-regional therapy with systemic therapy in unresectable HCC patients will more mature and become standardized in the next 5 years, and we believe that more studies will be conducted in the future to compare the safety and efficacy of loco-regional therapy combined with immunosuppressive agents versus sorafenib in order to maximize the clinical benefit .…”
Section: Discussionmentioning
confidence: 99%
“…Also, Zhang et al showed that the sequential treatment with regorafenib followed by sintilimab in a Sorafenib-Refractory hepatocellular carcinoma patient achieved a CR in their case report [ 22 ]. The significant highlight of the present case study is that it demonstrates that the combination of regorafenib plus sintilimab administered in an MSS stable CRC patient refractory to previous lines of treatment achieved CR and stable disease culminating antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported an advanced HCC case with liver recurrence and lung metastasis 18 months after radical resection, which was completely relieved after treatment with sorafenib followed by regorafenib plus sintilimab. 21 Based on our experience of using TKIs and ICIs, we describe a special case with skull and lung metastasis, and portal vein invasion, classified as IIIb in CNLC system and stage C in BCLC system, which was successfully managed by systemic therapy, with a review of the related literature. These findings will hopefully contribute to the therapeutic options available for treatment of advanced HCC, particularly for skull metastasis.…”
Section: Introductionmentioning
confidence: 99%